MISKONSEPSI GURU BIOLOGI PADA MATERI SISTEM RESPIRASI DI SMA NEGERI SE-KABUPATEN LABUHANBATU - Nurhakima Ritonga; Novi Fitriandika Sari; Halimah Sakdiah Boru Gultom (IKIP PGRI Pontianak, 2021)
This Research aims to analyze teacher misconception about the respiratory system material in SMA Negeri as Labuhanbatu District and to identify whether there is misconception in biology teacher. This research was conducted in SMA Negeri as Labuhanbatu Regency. The population in this research is all teachers of SMA Negeri in Labuhanbatu District, and the sample amounted to 24 teachers. The type of research was descriptived research method to a study that investigates teacher respondents based on understanding the concept and misconception of the Respiration System material. The instrument of this research using a two-dimensional diagnostic test of 15 questions. The results showed that misconception occurred in the teacher that only one concept that experienced misconception on the sixth concept is the concept of invertebarata animal respiratory system (insect) that is with values (-0,09).